Wanting Sheila dead - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books, 2010)
Sheila Dunham is a gossip columnist's dream--she's famous, loud and, to most who meet or see her, deeply offensive. As a result, she's been fired from every job on television she's ever had--first as a serious journalist, then as a personality, finally as a reality show judge. Now she's producing and hosting her own reality show, "America's Next Top Anchor,' shot in her hometown of New Fenwick, Connecticut. Everyone she employs is terrified of her; everyone one else hates her. And everybody seems to want Sheila dead. Finally it seems someone has decided to try. After millions of dollars of jewels are stolen from her home, she is found beaten into unconciousness, next to the murdered body of a local girl. If nothing else, her show's ratings are going to improve. Gregor Demarkian, a retired FBI agent, is already scheduled to appear on her show but he's going to consult on the biggest murder case to hit that part of Connecticut since the Revolutionary War. But how do you narrow down the suspects when the victim was hated by everyone?